(untitled) (Research, Society and Development, 2023)
Objective: To develop and evaluate a game about the control of Leishmaniasis, based on action research, as one of the coping strategies for this zoonosis. Methodology: it was based on the fundamentals of participatory action-research, which considers fundamental the participation of the subjects involved both in the knowledge production process and in decision-making. The first step was to hold a conversation circle with the students and their teachers to discuss the most popular games among them and the gathering of prior knowledge along with a theoretical presentation on the subject with students from the municipal school of basic education in the city de Girau do Ponciano-AL, where the knowledge before and after presentation of the theme among students about Visceral Leishmaniasis was analyzed. Results: Based on the analysis of the data obtained, the theoretical and methodological foundation of action research was used, namely, detection of the problem, interaction, monitoring of decisions and actions; problem solving; level of awareness to plan and apply a participatory educational intervention using a game for students from other schools. Conclusion: This research addressed the problem of Zoonoses, with emphasis on Leishmaniasis in a more contextualized and fun way through an educational game, to draw the attention of students and thus motivate them to be agents of multiplication of this knowledge in their Community.